2020
DOI: 10.1007/s10140-020-01797-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shelter-in-place on emergency department radiology volumes during the COVID-19 pandemic

Abstract: Purpose The coronavirus disease 2019 (COVID-19) pandemic has led to significant disruptions in the healthcare system including surges of infected patients exceeding local capacity, closures of primary care offices, and delays of non-emergent medical care. Government-initiated measures to decrease healthcare utilization (i.e., "flattening the curve") have included shelterin-place mandates and social distancing, which have taken effect across most of the USA. We evaluate the immediate impact of the Public Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 9 publications
6
34
0
Order By: Relevance
“…These exams compose 69% of all ED CT C/A/Ps normally and their decline likely reflects the aforementioned decrease in civilian movement due to stay-at-home orders. The UC health system study demonstrated similar findings [5]. Since the volume trough in mid-April, the preliminary volume data has been trending upward as demonstrated in Fig.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These exams compose 69% of all ED CT C/A/Ps normally and their decline likely reflects the aforementioned decrease in civilian movement due to stay-at-home orders. The UC health system study demonstrated similar findings [5]. Since the volume trough in mid-April, the preliminary volume data has been trending upward as demonstrated in Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Combined with the 46% decrease in ED imaging volume at our system during this period, the relatively flat, low-volume curve of the new cases in the nine counties supports the anecdotal idea that strictly from an ED imaging utilization perspective the northeast Ohio region was less impacted by the direct health effects of the COVID-19 pandemic and more impacted by the policies set forth to curtail its spread. In contrast, a similar study conducted at five University of California (UC) health centers demonstrated a 35% overall decrease in ED imaging volumes during a similar timeframe [5]. At the time of this writing, California has thus far seen the second highest number of positive COVID-19 cases in the country compared with Ohio, which has the 16th highest.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…While several hospitals found a decreasing trend in general trauma admissions from February to April 2020, none of these studies thoroughly evaluated the effects on emergent operative cases or changes in mechanisms of injury. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18…”
Section: Discussionmentioning
confidence: 99%
“…Singaporeans reduced their healthcare utilization by 23% in terms of total out-of-pocket healthcare spending. During the pandemic, there was a similar decrease in healthcare utilization in the U.S.: 32-40% in Emergency Department (ED) radiology volumes [33] and 49% in acute ischemic stroke patients. [34] Delaying healthcare is associated with longer hospital stays and poor health outcomes in the future.…”
Section: Methodsmentioning
confidence: 98%